Electronic and nuclear magnetic anisotropy of cobalt-doped ZnO single-crystalline microwires. (January 2019) - Savoyant, A.; Pilone, O.; Bertaina, S.; Delorme, F.; Giovannelli, F.
Abstract: Using electron paramagnetic resonance (EPR), we investigate the electronic and nuclear magnetic properties of ZnO:Co single crystals, grown by the optical furnace method. The high crystal quality of the studied samples allows for the determination of the full hyperfine and g tensors. We explain how the local magnetic anisotropy of the Co 2+ impurities is used as a very fine probe for the local symmetry and crystal quality of the host. The temperature- and power-study of EPR intensities recorded in three static- and microwave-field configurations give a qualitative insight into the dynamics of spin-lattice and spin-spin relaxations. In addition, in the context of nanostructures, we explain how a detailed analysis of the intensities anisotropy can reveal the proportion of ordered and disordered phases. Highlights: Paramagnetic ZnO:Co has highly anisotropic magnetic properties, both arising from nuclear and electronic spin. The spin-lattice relaxation time is proved to be anisotropic, with stronger coupling within the hexagonal plane. The study of the EPR intensity anisotropy allows for separating signal arising from ordered and disordered phases of ZnO:Co nano-object.